Simultaneous DNA-based diet analysis of breeding, non-breeding and chick Adélie penguins - McInnes, J.; Emmerson, L.; Southwell, C.; Faux, C.; Jarman, Simon (The Royal Society Publishing, 2016)
© 2016 The Authors. As central place foragers, breeding penguins are restricted in foraging range by the need to return to the colony to feed chicks. Furthermore, breeding birds must balance energetic gain from self-feeding with the costs of returning to provision young. Non-breeding birds, however, are likely to be less restricted in foraging range and lack the high energy demands of provisioning, therefore may consume different prey to breeders. We used DNA dietary analysis to determine whether there was a difference in provisioning and self-feeding diet by identifying prey DNA in scat samples from breeding and chick Adélie penguins at two locations in East Antarctica. We also investigated diet differences between breeders and non-breeders at one site. Although previous work shows changing foraging behaviour between chick provisioning and self-feeding, our results suggest no significant differences in the main prey groups consumed by chicks and breeders at either site or between breeding stages. This may reflect the inability of penguins to selectively forage when provisioning, or resources were sufficient for all foraging needs. Conversely, non-breeders were found to consume different prey groups to breeders, which may reflect less restricted foraging ranges, breeders actively selecting particular prey during breeding or reduced foraging experience of non-breeders.